Assessment Of Pure Tone Hearing Threshold In Niddm & Its Comparison With Healthy Individual (Journal of Pharmaceutical Negative Results, 2022)
Aim: To assess whether patients of NIDDM have a higher incidence of sensorineural hearing loss.Methodology: A cross-sectional study was conducted included 100 participants such that 50 were diabetics and another werenondiabetics. Pure Tone Audiometry was performed on the patient, and the results were assessed by comparing them to the patient'sdiabetes duration. The IBM SPSS version 20 software was used for all data analysis. The tables were created using cross tabulation andfrequency distribution.Results: On comparing the degree of hearing loss between both the groups and the mean hearing threshold of both the ears with durationof diabetes it was found that distribution of degree of hearing loss between the cases and control was significantly different.Conclusion: The study concluded that age had the direct association with the pure tone threshold level which means by increasing theage of the diabetes patients, hearing loss also increases as revealed by the significant p value of <0. 005.